$$-2^{2} - (-2)^{2} -2^{2} = $$

Incorrect.
[[snippet]]
Carefully check your work.

Incorrect.
[[snippet]]
You may have gotten this answer if you thought that exponents apply to negative signs in front of numbers. This is a common misconception. Remember, exponents only apply to what they are directly on:
> $$-2^2 = -(2\cdot2) = -4$$
> $$(-2)^2 = (-2)(-2) = 4$$

Incorrect.
[[snippet]]
You may have gotten this answer if you thought that exponents apply to negative signs in front of numbers. This is a common misconception. Remember, exponents only apply to what they are directly on:
> $$-2^2 = -(2\cdot2) = -4$$
> $$(-2)^2 = (-2)(-2) = 4$$

Incorrect.
[[snippet]]
Carefully check your calculations.

Correct.
[[snippet]]
The key here is to remember that exponents only apply to what they are directly on. They will not apply to negative signs in front of numbers unless the negative is inside parentheses that are to that exponent.
> $$-2^{2} - (-2)^{2} -2^{2}$$
>> $$ = -4 - 4 -4$$
>> $$ = -12$$

-16

-12

-8

-4

4